Geoelectric evaluation of groundwater potential within sunshine garden estate, akure southwestern Nigeria - Bello, Rereloluwa; Ajayi, Toluwaleke (International Journal of Physical Research, 2019)
The Vertical Electrical Resistivity surveys in the Sunshine Garden Estate have contributed to a better understanding of the basement complex of Southwestern Nigeria. Nine (9) vertical electrical sounding (VES) using the Schlumberger electrode array were interpreted and the results shows three (3) subsurface geoelectric layers within the study area. These are the weathered layer, topsoil, fresh/fractured basement. Groundwater pockets such as fractured zones, valley fills/basement depressions, and weathered zones were delineated in the study area. Weathered/partially weathered layer and weathered basement/fractured basement were the two major aquifer mapped out and these aquifers are characterized by thick overburden, found within basement depressions. The groundwater potential of the study area was zoned into low, medium and high potentials. Zones where the overburden thickness (which constitutes the main aquifer unit) is greater than 13m and of low clay composition (average resistivity value between 200 - 400â„¦m) are considered zones of high groundwater potential. Area where the thickness of the aquifer ranges from 11-13m with less clay composition are considered to have medium groundwater potential and the areas where the thickness of the aquifer is less than 11m are considered to have a low groundwater. The VES station underlained by high and medium groundwater potential zones are envisaged to be viable for groundwater development within the area.Â Â